THE EFFECTIVENESS OF USING OF STORYTELLING AND GTM IN TEACHING READING - Awaludin Rizal; Mujahid Taha; Ali Ajam (EDUKASI, 2022)
In reading comprehension, there are some problems appear and students unable to read efficiently and effectively. The problems found were unvaried of teaching method. This study investigated the effect of teaching reading comprehension through grammar translation method and storytelling to the second grade students of state senior High school 4 Ternate. This study was categorized as experimental research, in this study researcher used quasi experiment in finding out the answer of the problem of the study. There were two classes becoming sample of study namely XI-1 as storytelling group and XI-6 as grammar translation method with the total number of students are 56. The sample of the study is determined using population research random sampling technique. Both of groups were given pretest before treatment. Then the students of the first experimental group was taught using storytelling and the second control group was taught using grammar translation method. Finally, the researcher gave post-test to both groups. The finding showed that the mean of the reading comprehension ability of the students before (54.82) and after (78.21) taught by using storytelling. Then, the mean of the reading comprehension ability of the students before (50.89) and after (72.50) taught by using grammar translation method. The p value was lower than the significance level (0.004˂0.05). so the alternative hypothesis was accepted. Hence, there is a significant difference between the reading comprehension ability of the students taught by using Storytelling and that of the students taught by using Grammar Translation Method.